Giant epignathus of the palate: a case report - Marcelo P. Menezes Filho; Nábia Maria M. S. Simão (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACTEpignathi are congenital malformations, with a high level of mortality due to their obstructive mechanism and respiratory involvement. Most of them are benign; however, cases of malignant epignathus have been described. The possibilities of malignancy increase in the presence of neuroepithelium, an important confounding factor. Epignathus is described in a newborn, besides its clinical and histopathological study. Surgery with complete resection is the definitive treatment. Residual tissue is linked to recurrence, curiously without increasing the risk of malignancy.